Primary Retroperitoneal Seminoma—An Uncommon Presentation With Significant Implications - S. Sain; S. Tripathi; N. Bakshi; S. A. P. Das; S. Nundy (Case Reports in Surgery)
Conclusion: This case highlights the diagnostic and therapeutic challenges of primary retroperitoneal seminoma. A multidisciplinary approach, including accurate histopathological diagnosis and a combination of chemotherapy and surgery, is essential for optimal management. Early diagnosis and tailored treatment strategies significantly improve patient outcomes.